2020
DOI: 10.3762/bjoc.16.55
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and in situ use of unstable N-alkyl α-diazo-γ-butyrolactams in RhII-catalyzed X–H insertion reactions

Abstract: N-Alkyl α-diazo-γ-butyrolactams, previously found to be unstable and to undergo unproductive dimerization to bishydrazones, were successfully converted immediately to various X–H insertion products with alcohols, aromatic amines and thiols via an in situ RhII-catalyzed reaction. With aliphatic amines or unreactive, sterically hindered anilines, the reactions tended to yield enamine adducts.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The arsenal of diazo compounds 1 a – i selected for this study has been reported previously as prepared via the recently developed ‘sulfonyl‐azide‐free’ (SAFE) protocol ( vide infra ) [10–12] . α‐Diazo‐γ‐butyrolactams 1 j – n were prepared via the Danheiser diazo transfer protocol using 4‐nitrobenzene sulfonyl azide as diazo transfer reagent [13,14] . It should be noted that all aforementioned diazo compounds are stable to storage except for 1 j which undergoes a rapid dimerization [14] and had, therefore, been used immediately [13] in the subsequent Rh(II)‐catalyzed S−H insertion reaction without isolation (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The arsenal of diazo compounds 1 a – i selected for this study has been reported previously as prepared via the recently developed ‘sulfonyl‐azide‐free’ (SAFE) protocol ( vide infra ) [10–12] . α‐Diazo‐γ‐butyrolactams 1 j – n were prepared via the Danheiser diazo transfer protocol using 4‐nitrobenzene sulfonyl azide as diazo transfer reagent [13,14] . It should be noted that all aforementioned diazo compounds are stable to storage except for 1 j which undergoes a rapid dimerization [14] and had, therefore, been used immediately [13] in the subsequent Rh(II)‐catalyzed S−H insertion reaction without isolation (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Known diazocarbonyl compounds 1 a – n were prepared according to literature procedures,[ 10 , 11 , 12 , 13 , 14 ] other reagents were obtained from commercial sources and used without any additional purification. Solvents were distilled over suitable drying agents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…o -Substitution in the aryl group perturbs that conjugation and makes such systems more ‘ N -alkyl-like’ [ 128 ]. In order to be able to use such unstable α-diazo-γ-butyrolactams in subsequent transformations, a convenient, one-pot protocol has been developed that does not require the isolation of the diazo compounds in the interim [ 129 ].…”
Section: α-Diazo Lactamsmentioning
confidence: 99%